Challenges and Obstacles in the Standardization and Harmonization of Fatwa in Islamic Finance Industry and Way Forward - Devi, Abrista; Hamid, Baharom Abdul (SMART Insight, 2024)
The purpose of this paper is to explore the potential benefit, challenge and obstacles in the standardization and harmonization of fatwa in Islamic finance industry. This paper is also intended to formulate strategies to release the standardization and harmonization of fatwa. This study employs qualitative approach and reviews literatures that are relevant to the research objective. The finding indicates that the potential benefit of harmonization of fatwa are efficient and manageable regulation and control, IFIs will have a set of reporting and guideline standards, contribute to IFIs’s growth, enhance public and IFI’s confidence, and lead to greater transparency. Meanwhile, the challenges to harmonize the fatwa can be divided into four main problems, technical, governance, human resource, and regulation. Technical problems comprise difference of opinion in ijtihad and fatwas, the absence of consensus (ijma’), and national cultural specificities. Governance consist of international fatwa bodies are only followed by selected member countries, difference in sharia compliance governance model among countries, and difference level of Islamic finance industry growth among countries. Human resource involves lack of inclusivity, lack of professionals, personal/group interest. Finally, regulation be made up of lack of support from regulators, enforcement problem, and lack of legal system. This study also purposes some important strategies to release the standardization of fatwa and some recommendations for future studies.